2020
DOI: 10.1371/journal.pone.0236918
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge, attitude, and perceptions towards the 2019 Coronavirus Pandemic: A bi-national survey in Africa

Abstract: The current Coronavirus (COVID-19) pandemic has impacted and changed lives on a global scale since its emergence and spread from China in late 2019. It has caused millions of infections, and thousands of deaths worldwide. However, the control of this pandemic still remains unachievable in many African countries including Egypt and Nigeria, despite the application of some strict preventive and control measures. Therefore, this study assessed the knowledge, attitude, and perceptions of Egyptians and Nigerians to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
124
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(174 citation statements)
references
References 24 publications
41
124
2
7
Order By: Relevance
“…The level of education, background, and nationality greatly affected the perception of global and community response to curbing the spread of COVID-19 and preventing the occurrence of any future pandemic. Furthermore, female participants were 1.59 times (95% CI: 1.27-1.99; p < 0.001), more likely to have a positive attitude towards COVID-19 than males, and Nigerians were 11times (95% CI: 7.57-13.47; p <0.001) more likely to have a positive attitude than Egyptians (19). In a study conducted by Yanti et al, (2020) (18) in Indonesia, found that the respondents' educational and occupational attainment, such as bachelor graduate or civil servant, in uenced their positive attitudes towards social distancing.…”
Section: Level Of Kap On Community-based Interventions For Preventingmentioning
confidence: 97%
See 4 more Smart Citations
“…The level of education, background, and nationality greatly affected the perception of global and community response to curbing the spread of COVID-19 and preventing the occurrence of any future pandemic. Furthermore, female participants were 1.59 times (95% CI: 1.27-1.99; p < 0.001), more likely to have a positive attitude towards COVID-19 than males, and Nigerians were 11times (95% CI: 7.57-13.47; p <0.001) more likely to have a positive attitude than Egyptians (19). In a study conducted by Yanti et al, (2020) (18) in Indonesia, found that the respondents' educational and occupational attainment, such as bachelor graduate or civil servant, in uenced their positive attitudes towards social distancing.…”
Section: Level Of Kap On Community-based Interventions For Preventingmentioning
confidence: 97%
“…Six studies (4,7,16,(18)(19)(20) met the inclusion criteria for this systematic review. All the included studies were conducted during the COVID-19 pandemic and published between the months of April and August, 2020.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations